University students' digital spaces in online learning communities: Implications for understanding, protecting and maintaining privacy - Özer Şanal, Seda; Çiçek, Büşra (John Wiley and Sons Inc, 2024)
In addition to learning effectively and effectively in online learning communities (OLCs), students must be in a secure environment and privacy must be respected. The study aimed to identify privacy violations that university students encounter in OLCs, and identify recommendations and some strategies to implement to ensure privacy at the OLC. A qualitative research method was applied in the study. First, focus group interviews were conducted with a total of 108 students who participated actively in the OLC. After analysing the interview data, a privacy violations report (RPV-OLC) was prepared at the OLC. According to the RPV-OLC, a problem description for the Delphi technique was designed and 17 experts were identified for the interview. Delphi panels with experts were completed in 5 months. The content analysis process was used for the data obtained. Students said they encountered information sharing and access, access to information, system/course settings, resistance to negotiations, communication problems and lack of knowledge. On the other hand, experts suggest that different suggestions and strategies could be implemented to ensure privacy in the OLC, such as partial privacy, mutual trust, contextual privacy agreements, role-based or anonymous identity use, and privacy education. The study focused on defining the concept of privacy and student privacy violations in online learning environments and providing solutions for educators, students and system administrators. Practitioner notes What is already known about this topic Digital learning environments pose a threat to the privacy of students. The fact that privacy violations in the OLC can trigger concerns among students has a negative impact on learning processes. There is high interest at the moment in how to plan the most effective teaching in online learning environments—but privacy is being neglected. What this paper adds This article explains the privacy violations university students encounter at the OLC. This document contains guidelines on how to mitigate and prevent privacy violations in OLC. The results of the study also provide suggestions for privacy protection at the OLC. Implications for practice and/or policy It is important that the instructors who participate in the OLC are informed about the necessary measures, rules, principles, activities and follow-up measures to protect their personal privacy. If we can overcome students' concerns about privacy violations at the OLC, we can create more comfortable learning spaces. The aim of learning should not only be to peak performance; the most important responsibility of educators or system administrators is to preserve each student's private space, while at the same time achieving the best performance. © 2023 British Educational Research Association.
Keywords: Delphi interview; digital privacy; online learning community; personal privacy; university students